Pemanfaatan SFCL tipe Bridge untuk Meningkatkan Stabilitas Transien Microgrid dan Economic Feasibility - Roy Bayu Negara; Fransisco Danang Wijaya; Lesnanto Multa Putranto; Mohd. Brado Frasetyo (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2023)
Currently, renewable energy (RE) generators are widely used by society to reduce emissions. Therefore, a RE-sourced microgrid system coexisting with conventional energy is being developed. However, these electrical energy systems experience transient disturbances such as short circuits, load increase, and decrease in generator output. These disturbances can result in voltage drops and frequency instability. Therefore, efforts are needed to maintain system stability by using a superconducting fault current limiter (SFCL). The SCFL selection is based on its capability to limit the fault current and its speed in providing protection during transient disturbances. The utilized SFCL model is the bridge-type SFCL with two inductors as its main components. Under normal conditions, the current flows through two inductors, and when a fault occurs, the current will go through one inductor. This research was conducted in a scenario where a fault occurred. The voltage value without a bridge-type SFCL during the fault condition was 2.5 V. When a bridge-type SFCL was used, the voltage value was 207 V. Without a bridge-type SFCL, the measured current was 30 kA, whereas the measured current was 1.1 kA with one. The frequency range was 49.7 Hz - 50.2 Hz without bridge-type SFCL and 49.9 Hz - 50.1 Hz with bridge-type SFCL. This research also added an economic feasibility calculation to determine the microgrid system feasibility when using bridge-type SFCL. The calculation consisted of four parts, i.e., net present value (NPV), profitability index (PI), discounted payback period (DPP), and internal rate of return (IRR). Economic feasibility was obtained for an NPV value of US6,865,405, a PI value of 2.4, a DPP value of four years, and an IRR value of 28.59%. When the obtained value is compared to the feasibility standard, it is determined that a microgrid with SFCL is feasible.